Neurocognitive functions after carotid endarterectomy (CEA) under regional and general anesthesia - Mazul-Sunko, Branka; Tadinac, Meri; Hromatko, Ivana Čima, Ana; Gvozdenović, Aleksandra Ivanec, Željko; Kličan, Katarina, Krolo, Helena (2007)
Neurocognitive functions after carotid endarterectomy (CEA) under regional and general anesthesia
Projekt MZOS
ENG